2022
DOI: 10.1155/2022/1061045
|View full text |Cite
|
Sign up to set email alerts
|

GuitarPD: A Randomized Pilot Study on the Impact of Nontraditional Guitar Instruction on Functional Movement and Well-Being in Parkinson’s Disease

Abstract: Playing musical instruments may have positive effects on motor, emotional, and cognitive deficits in patients with Parkinson’s disease (PD). This pilot study examined the feasibility of a six-week nontraditional guitar instruction program for individuals with PD. Twenty-six participants with idiopathic PD (Age: 67.22 ± 8.07; 17 males) were randomly assigned to two groups (intervention first or 6 weeks of usual care control exposure) with stepwise exposure to the guitar intervention condition with cross-over at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
5
0
2
Order By: Relevance
“…The effects of music therapy on apathy and mood in this study are consistent with prior research 16,22,23 and can be explained by understanding the two primary effects of music-based interventions. 43 Music’s impact on mood and emotion gives it the ability to improve one’s quality of life and overall well-being.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The effects of music therapy on apathy and mood in this study are consistent with prior research 16,22,23 and can be explained by understanding the two primary effects of music-based interventions. 43 Music’s impact on mood and emotion gives it the ability to improve one’s quality of life and overall well-being.…”
Section: Discussionsupporting
confidence: 88%
“…22 A pilot, feasibility study of a group guitar instruction program found improvements in depression, anxiety and quality of life. 23 As a secondary outcome, quality of life has been noted to improve with various music-based interventions. 17,21 Limited studies have evaluated the impact of music therapy on caregivers of people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Die motorische Dysfunktion ist eine der häufigsten Komplikationen nach einem Schlaganfall, die sich in Taubheitsgefühlen und Schwäche der Gliedmaßen bis hin zu Lähmungen oder Krämpfen äußert [29]. [31].…”
Section: Schlaganfallunclassified
“…During an 18-week period, participants with PD were randomly assigned to treatment and control groups and assessed at the outset and every 6 weeks on a variety of self-reported and performance-based measures, including mood, social participation, cognition and arm and hand function. Results showed that the group guitar lessons produced clinically and statistically significant improvement in participant mood and anxiety ( Bastepe-Gray et al, 2022 ).…”
Section: Itf Case Studiesmentioning
confidence: 99%
“…In keeping with the goals of the ITF, Guitar PD sought impact via multiple methods of dissemination. For example, study results were shared via a peer-reviewed paper ( Bastepe-Gray et al, 2022 ) and invited scientific talk. The Impact Team also developed a series of ideas to share this work with PD advocacy groups and clinicians, including suggesting specific ways to include guitar lessons in treatment plans.…”
Section: Itf Case Studiesmentioning
confidence: 99%